x + y = z x − y = z x y = z Find x , y , z . Enter your answer as 3 x + 2 y + z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x + y = z Eq. (1)
x − y = z Eq. (2)
x y = z Eq. (3)
Eq. (1) − Eq. (2):
( x + y ) − ( x − y ) = z − z 2 y = 0 ⟹ y = 0
Substitute this into Eq. (3):
0 x = z ⟹ z = 0
Finally, substitute both values to find x :
x + 0 = 0 ⟹ x = 0
x = y = z = 0 , therefore:
3 x + 2 y + z = 3 ( 0 ) + 2 ( 0 ) + 0 = 0
Adding first two equations we get 2 x = 2 z or x = z . Thus we get y = 0 .
From the third equation we get x y = z or 0 = z .
Thus x = y = z = 0 .
Hence the value of 3 x + 2 y + z = 0 .
Squaring the first two equations we get:
z 2 = ( x + y ) 2 = x 2 + 2 x y + y 2 , z 2 = ( x − y ) 2 = x 2 − 2 x y + y 2
Taking these from each other: 4 x y = 0 , z = x y ⇒ 4 z = 0 ⇒ z = 0
Going back to the original equations:
x + y = z , x − y = z ⇒ 2 x = 2 z ⇒ x = 0
Also x − y = z ⇒ y = 0
So x = y = z = 0 ⇒ 3 x + 2 y + z = 0
Problem Loading...
Note Loading...
Set Loading...
Given x+y=z; x-y=z; Therefore ; x+y=x-y; Due to which 2y=0; So we can conclude that x=0(as x-y=0)and z=0(as xy=z)